"Komitmen Beragama Islam", "Konsep Diri" dan "Regulasi Diri " Para Pengguna Narkoba - Agus Sofyandi Kahfi (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2016)
The aim of this study is to obtain empirical data about corelation between Islamic religious commitment with self concept and self regulation. Moreover, the aim of this study to obtain empirical description of the Islamic religious commitment with its dimensions wich impact the self concept and self regulation of addicted indiviuals with tendencies to relapse. The method used by this study was causal comparative modeling technique which processed using multiple regression techniques. The Subject of this study is 30 addicted individual with intensive rehabilitation program. Measuring instrument used were questionnaires compiled Islamic religious commitment based on the three basic teaching of Islam, Fits's (1971) self concept and modified Zimmerman's self regulation (2000). Result from this study shows that Islamic religious commitment with its dimension has a significant relation with self concept (a 0.627) and (a 0.782) with self regulation,and has influence together on self concept by 0.41% and on self regulation by 62.1%.Keywords: Islamic Religious Commitment, Self Concept, Self Regulation, Addicted, RelapseÂ